PELATIHAN IBM MENJAHIT BUSANA GAMIS DENGAN POLA METODE CUPPENS GEURS SEBAGAI PEMBERDAYAAN EKONOMI IBU-IBU DASAWISMA DI KELURAHAN TLOGOSARI - Dian Ratu Ayu Uswatun Khasanah; Eem Kurniasih; Lusi Rachmiazasi Masduki; Edi Prayitno (LPPM Universitas Bina Bangsa, 2023)
Sewing is an activity that is timeless. The number of fashion stores that offer ready-made clothes does not necessarily satisfy buyers. Some are uncomfortable on the body because they don't fit the size, some are not suitable models, and other problems. From this sewing skills are needed. Even skills that are often honed will make you confident, so that it can be used as an improvement in the family economy for dasawisma mothers. The products produced are in demand by fellow friends, and one day they are more developed by selling their products. Starting from that, when partners put forward for sewing training, it was chosen to use the Cuppens Geurs method because it was simpler, more common, and easy to practice. Implementing community service this sewing training lasts for 6 months by optimizing the andragogy training model training program, namely 70% practice and 30% theory. Participants focused more on practical activities using the CG (Cuppens Geurs) method pattern that has been adapted to their respective models that have been selected by partners. The optimization of the program includes the manufacture of women's clothing, namely Gamis clothing. The service activities that have been achieved in this program are dasawisma mothers from Tlogosari Semarang village, from Dasawisma Durian, Dasawisma Pomegranate, Dawis Dahlia, and from the Sunan Kalijaga recitation group to produce gamis products